2020
DOI: 10.1186/s13063-019-4043-7
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor rehabilitation to improve functional outcome and quality of life after surgery for rectal cancer: study protocol for a randomized controlled trial (FORCE trial)

Abstract: Background: After low anterior resection (LAR), up to 90% of patients develop anorectal dysfunction. Especially fecal incontinence has a major impact on the physical, psychological, social, and emotional functioning of the patient but also on the Dutch National Healthcare budget with more than €2000 spent per patient per year. No standardized treatment is available to help these patients. Common treatment nowadays is focused on symptom relief, consisting of lifestyle advices and pharmacotherapy with bulking ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(71 reference statements)
1
14
0
Order By: Relevance
“…Although surgeons worldwide are informed about LARS by societies, congresses and the scientific literature, there are still large gaps in knowledge about the treatment of LARS. A limited number of randomized controlled trials for LARS, mainly carried out by surgeons, are available [75,80–82] emphasizing the lack of sound evidence. The recommendation for the present guidance is therefore partly based on expert opinion.…”
Section: Section Viii: the Patient Perspectivementioning
confidence: 99%
“…Although surgeons worldwide are informed about LARS by societies, congresses and the scientific literature, there are still large gaps in knowledge about the treatment of LARS. A limited number of randomized controlled trials for LARS, mainly carried out by surgeons, are available [75,80–82] emphasizing the lack of sound evidence. The recommendation for the present guidance is therefore partly based on expert opinion.…”
Section: Section Viii: the Patient Perspectivementioning
confidence: 99%
“…psychologists and physical therapists) [19]. For instance, early results demonstrated that cognitive behavioural therapy reduced levels of distress in patients with CRC [42], and for a selection of (rectal cancer) patients, pelvic floor rehabilitation might provide relief in LARS-like symptoms [43].…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of the patients with major LARS did not diminish over time, which is why an improved focus on early screening of LARS-like complaints is necessary to identify patients in need and provide the necessary supportive care. Early results of the FORCE trial showed promising results of protocolised pelvic floor rehabilitation in selective patients with rectal cancer suffering of LARS [43]. Besides that, medication (laxatives/loperamide) or rectal irrigation could provide relief of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…24 Seeing that a withdrawal/replacement rate of 50% was anticipated, [12][13][14][15][16][17] 128 patients were included. 18 Primary analysis was done in the intention-to-treat population, supplemented by a per-protocol analysis, including patients who participated in PFR without serious protocol deviations and controls who did not participate in any form of PFR during follow-up. The mean change in Wexner scores was compared between groups by analysis of covariance.…”
Section: Discussionmentioning
confidence: 99%
“…A preoperative measurement (M1) with the same questionnaires as used continuously through the study administered before surgery reduced inclusion rates to such an extent that it had to be removed from the study protocol. 18 Randomization took place after completion of M2. Subsequently, patients either continued with usual care without PFR or participated in a standardized PFR program for 3 months, after which the primary endpoint (M3) analysis was done (Fig.…”
Section: Procedures and Course Of The Studymentioning
confidence: 99%